The Influence of Genotypes and Culture Medium on In Vitro Proliferation in Heuchera spp. - Paula OROS; Corina CĂTANĂ; Cristian Cătălin CIOBANU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture)
The genus Heuchera includes perennials prized worldwide in gardens for their ornamental foliage and flowers. This study aimed to assess the in vitro proliferation efficiency of two Heuchera genotypes under different culture media conditions of two Heuchera genotypes, Heuchera villosa 'Silver Gumdrop' (SG) and Heuchera x hybrida 'Timeless Orange' (TO) by testing different culture media. The in vitro culture was initiated on two culture medium compositions: Murashige & Skoog, 1962 (MS) and Murashige & Skoog, 1962 with Gamborg B5 vitamins (MSB5). The regeneration rate of explants was evaluated. In the multiplication stage, in addition to the two culture medium compositions, the influence of cytokinin benzylaminopurine (BAP) on the plantlets proliferation was tested. Among the two culture media used at initiation, MSB5 resulted in regeneration rates of 96.67% for SG and 93.33% for TO. Similar situation was observed for shoot proliferation. By using MSB5 the highest shoot proliferation was obtained for both genotypes: 5.92 shoots for SG and 4.13 for TO respectively. However, supplementing the culture medium with BAP resulted in high vitrification rates. The results demonstrate the protocol's efficiency in producing large quantities of healthy, uniform plants within a reduced cultivation period. Both culture media led to high production efficiencies, which recommends multiplication in Heuchera spp. by micropropagation.